Parameter Characteristics of Projective Synchronization of two Gyroscope Systems with Different Dynamical Behaviors - Min, Fuhong; Luo, Albert C.J. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, parameter characteristics of the projective synchronization for two gyroscopes with different dynamical behaviors are investigated. The projective synchronization conditions are presented from the theory of discontinuous dynamical systems. From such synchronization conditions, the parameter characteristics for partial and full projective synchronizations for two gyroscope systems are studied. The full projective synchronization can be achieved exactly in finite time instead of asymptotic synchronization in the traditional projective synchronization. The scaling factors in such synchronization are observed through numerical simulations.